POLA AGIHAN MATAAIR DI SEBAGIAN LERENG TIMUR GUNUNG MARAPI - Almegi Almegi; Endah Purwaningsih (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This research aims to determine the distribution pattern and characteristics of the springs in each morphological unit on the eastern slopes of Mount Marapi, West Sumatera Province. The approach in this research in descriptive quantitative with data collection through survey methods. The population in this research is all the springs in the area study with data collection carried out by systematic sampling based on altitude. Spatial analysis was carried out to analyze the pattern and characteristics of the springs and the chi square (x2) test to see differences in the distribution of spring in various geomorphological unit volcanic formations. The results of the analysis show that the pattern of springs in the study area does not form a spring belt perfectly with the most springs appearing around the break of slope, which is around the ​​displacement area between the morphology of the volcanic slope and the morphology of the volcanic foot. Based on the amount of discharge, there is no significant difference in the distribution of springs in various morphological units with a correlation coefficient of 0.425 at the 95% confidence level. Keywords : spring; springs belt; volcanic formation